Tears of the Clown: A Desk-Based Investigation into the use of Dramatherapy Practices to Promote and Foster Positive Adolescent Mental Health in Non-Clinical Settings - Milofsky, Josh (Trinity College (Dublin, Ireland). School of Education, 2021)
Education, and the promotion of positive Adolescent Mental Health, do not exist in separate expanses. Effective provision of pastoral care for students subsists as a core tenet of teaching and learning. There is a vast array of pedagogies available to an educator in disseminating this care, including methodologies incorporating Drama in a variety of presentations. The use of Drama in Education (DIE) practices to interrogate concepts of Mental Health in adolescent settings has been explored in previously conducted research. Equally, Dramatherapy exists as a form of Creative Arts Therapy (CAT) utilised in clinical settings and by professional dramatherapists in corrective capacities in diagnosis and treatment of defined mental health conditions. However, a gap exists in educational, psychological and drama-based theoretical discourse and praxis in the use of Drama, in non-clinical settings, to promote and foster Adolescent Mental Health. This desk-based study, conducted in the context of an extra-curricular Drama workshop in an Irish co-educational, private secondary school, seeks to investigate the use of Dramatherapy practices to promote and foster Adolescent Mental Health in a non-clinical setting. This promotion is significant; this research does not posit school settings as optimum locations for the conducting of dramatherapeutic practices as opposed to environments of professional care settings. Instead, the use of practices incorporating Dramatherapy principles to foster positive Adolescent Mental Health is examined. After exploring Adolescent Mental Health, Dramatherapy and Drama in Education as component theoretical paradigms within the contextual framework of this study, an intersection of these three modalities is introduced. Identified as a concentration on aesthetic distance, this research refers to this intersection as ‘The Bridge with Two Sides’. With this crossing point established, a workshop, person-centred in construction, is generated to further engage with the investigation of this study. This workshop, dramatherapeutic in nature, is based on integral conventions associated with Clowning principles and training. The findings of this study indicate that whilst practices incorporating Dramatherapy may be used in non-clinical settings to support, promote and foster Adolescent Mental Health, these settings are in no way appropriate for the conducting of actual therapy. This research highlights that the utilisation of Dramatherapy practices in a non-clinical setting, such as that of the research context identified, can result in the promotion and fostering of positive Adolescent Mental Health. The illustration utilised for this study can achieve this through an increase in a participant’s own sense of resilience and self-worth. The implications of these findings argue that the use of practices incorporating Dramatherapy principles in non-clinical contexts to promote positive Adolescent Mental Health are effective. This work also argues that such practices are employable by educators to effectively facilitate a greater sense of pastoral care. This is achieved through the privileging of a student’s own voice.
Keywords: Drama in Education; Education